Validation and Evaluation of Browser Forensics Using Digital Forensic Approach Based on the National Institute of Standards and Technology (NIST) Framework - Syukri, Muhammad; Riadi, Imam; Sutikno, Tole (Jurnal Teknik Informatika (Jutif), 2025)
Browsers have become essential applications in digital life alongside the advancement of internet technology. However, users’ low awareness of privacy security during web browsing can lead to the risk of data theft by malicious parties. This study analyzes digital traces in Google Chrome and Mozilla Firefox using a digital forensic approach based on the standards of the National Institute of Standards and Technology (NIST). The method involves four testing scenarios to compare digital traces in storage media (hard drive) and RAM between normal and private/incognito browsing modes. The objective of this research is to validate and evaluate previous findings conducted on the Linux operating system, using a different approach within a Windows environment. The experiment uses the same digital forensic tools to ensure data accuracy. This study contributes to the advancement of browser forensics by presenting a validated and reproducible framework for memory-based privacy evaluation, thereby supporting more accurate and systematic analysis of digital traces.